Neural network in medical application: A review - Wan Ishak, Wan Hussain; Siraj, Fadzilah; Othman, Abu Talib (2001)
Artificial Neural Networks or widely known as Neural networks (ANNs or NNs) is a computational paradigm that comprises of mathematical, statistical, biological sciences and philosophy. These paradigms formulate a formula to form a brain like function, called artificial neuron. Artificial neuron comprises of large number of computational processing elements called units, nodes or cells. Analogously, these processing elements mimic the processing elements of biological neuron. This paper discusses neural network as a powerful tool to enhance current medical prognostic techniques. One of the most popular learning algorithms that are backpropagation algorithm is discussed. Several applications of neural network in medical application are reviewed.